Coping with the Stress of Obesity - Sanjay Kalra; Komal Verma; Ashok Kumar; Nitin Kapoor (Journal of the Pakistan Medical Association, 2025)
Coping with chronic disease, such as obesity, is central to effective management. Coping skills enhancement, therefore, should be made part of obesity therapy. The AEIOU model, coupled with the five Bad Bs and five Positive Ps, allows health care professionals to integrate coping skills enhancement in routine care. Analysis and elimination of negative coping mechanisms, initiation and integration of positive skills, ongoing observation and use of opportunities for optimization, and upgradation of one’s understanding, allow enhancement of coping skills. This should be considered standard of care in all obesity management programmes. Keywords: Motivation, motivational therapeutics, obesity, person centred care, psychosocial